Co-hydrothermal carbonization of pomelo peel and PVC for production of hydrochar pellets with enhanced fuel properties and dechlorination. (15th January 2022) - Wei, Yingyuan; Fakudze, Sandile; Zhang, Yiming; Ma, Ru; Shang, Qianqian; Chen, Jianqiang; Liu, Chengguo; Chu, Qiulu
Abstract: Extremely high volatiles and excessive chlorine contents remained bottlenecks for the conversion of polyvinyl chloride (PVC) into eco-friendly solid fuel. In our work, we proposed the co-hydrothermal treatment (co-HTC) of pomelo peel (PP) and PVC under citric acid solvent at 220 °C. Properties of the PP/PVC blended hydrochars were assessed by elemental and proximate analysis, scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET), Fourier transform infrared (FTIR) analysis, thermogravimetric analysis (TGA) and single pellet combustion. In addition, gas chromatography - mass spectrometry (GC-MS) and FTIR were used to analyze the chemical features of process water obtained after the co-HTC process. Results showed that hydrochar obtained after co-hydrothermal carbonization by using 50% PP and 50% PVC (CA-HC-5:5) demonstrated the best higher heating value (22.58 MJkg −1 ), energy yield (51.76%) and dechlorination efficiency (93.50%). Moreover, CA-HC-5:5 was characterized by a finer texture suitable for pelletization, which could be due to PVC particles inserting into the pores of PP. In support of this phenomena, BET results showed that the surface area and quantity of N2 gas absorbed by PP were significantly reduced when co-treated with PVC. Hence, the results implied that PVC could be effectively co-valorized with lignocellulosic biomass to produce eco-friendly solid fuel. Graphical abstract: Image 1 Highlights: Pomelo peels provided porous skeleton for PVC condensation. Synergistic effects of PVC/pomelo peels during co-HTC led to >90% dechlorination. Pomelo peels/PVC hydrochars show excellent fuel properties and combustibility. Abundance of 5-HMFs and furfurals in HTC process water analyzed by GC-MS.